Keyakinan Epistemologis Siswa Lintas Level Akademik Terhadap Fisika - Lestari, Widji; Mansyur, Jusman; Werdiana, I Komang (Mitra Sains, 2015)
This research applied qualitative research which used descriptive method in order to describe the general epistemological beliefs of middle school students in two schools with different academic levels. The subjects of this research were the eleventh graders of SMA Al-azhar Palu and six the ninth graders of SMP Al-azhar Palu. The selection of respondents and the collection data of epistemological beliefs using EBAPS (Epistemological Beliefs Assessment for Physics Science). Interviews were carried out to elicit students’ epistemological beliefs information. Analysis showed that the two academic levels have the same beliefs on dimensional Structure of Scientific Knowledge (SSK), Nature of Knowing and Learning (NKL) and Real-Life Applicability (RLA), and have different beliefs on Evolving dimensions of Knowledge (EK) and Source of Ability to Learn (SAL).